Strategi meningkatkan pendapatan asli Daerah Kota Manado melalui pengelolaan pajak - Supit, Brain Fransisco; Lumingkewas, Elvis; Lambut, Adventinus (Academy of Education Journal, 2024)
The aim of this research is to 1) Analyze strategies for increasing Original Regional Income in Manado City through the management of Parking Tax; 2) Analyze the factors that hinder the Manado City Regional Revenue Agency in managing Parking Tax. The author uses qualitative research methods with SWOT analysis as a data analysis tool. The research results show that the Manado City Regional Revenue Agency has Strength and Opportunity (SO), so that its strengths and opportunities can be an advantage for the Manado City Regional Revenue Agency in increasing Original Regional Income through parking taxes. There are four strategic recommendations, namely: 1) Be firm in implementing parking tax sanctions and fines, 2) Improve parking tax services, 3) Improve parking tax communication and education, and 4) Increase parking tax supervision. Meanwhile, the inhibiting factors are: (1) Low discipline/compliance of parking taxpayers in paying taxes, 2) Low honesty/awareness of parking taxpayers in manipulating the amount of income turnover so that tax payments are low, (3) Limited number of human resources working and ineffectiveness of the joint task force in carrying out its main duties (4) Ineffective application of administrative sanctions such as fines, closure and sealing for tax objects that are late, in arrears or even do not pay parking tax, 5) Lack of supporting facilities such as operational vehicles, computers, laptops and printers.